Epstein-Barr virus infection induces bone resorption in apical periodontitis via increased production of reactive oxygen species. (September 2016) - Jakovljevic, Aleksandar; Andric, Miroslav; Miletic, Maja; Beljic-Ivanovic, Katarina; Knezevic, Aleksandra; Mojsilovic, Slavko; Milasin, Jelena
Abstract: Chronic inflammatory processes in periapical tissues caused by etiological agents of endodontic origin lead to apical periodontitis. Apart from bacteria, two herpesviruses, Epstein-Barr virus (EBV) and Human cytomegalovirus (HCMV) are recognized as putative pathogens in apical periodontitis. Although previous reports suggest the involvement of EBV in the pathogenesis of apical periodontitis, its exact role in periapical bone resorption has not yet been fully elucidated. We hypothesize that EBV infection in apical periodontitis is capable of inducing periapical bone resorption via stimulation of reactive oxygen species (ROS) overproduction. Increased levels of ROS induce expression of receptor activator of nuclear factor kappa B (NF-κB) ligand (RANKL). RANKL binding to receptor activator of nuclear factor κB (RANK) present on the surface of preosteoclasts induces their maturation and activation which consequently leads to bone resorption. The potential benefit of antiviral and antioxidant-based therapies in periapical bone resorption treatment remains to be assessed.